Relasi Dan Reposisi Agama Dan Negara - Sofyan Hadi (Ri'ayah: Jurnal Sosial dan Keagamaan, 2018)
That at this time developed various Discourses / Discourses on freedom and religious protection. On the one hand there are those who think that freedom is limited by the freedom of others. For those who embrace unlimited freedom, government policies that prohibit the activities of people or groups who are considered to taint a particular teaching are accused of violating human rights. As for those who embrace freedom with no limits, what is done by the government is considered correct, because in order to protect the religion from desecration by a particular person or group. Then how should relationships and repositioning that we will "construct" as citizens / religious people to address thinking, flow and religious ideology in Indonesia? left, integrated, compiled or even totally revolutionized.